(untitled) (Indonesian Journal of Agrarian Law, 2026)
Spatial planning functions as a regulatory instrument to ensure orderly and sustainable use of space. This study aims to evaluate the effectiveness of controlling the use of space in the tourism area of Tawangmangu Regency using the perspective of legal theory of Lawrence M. Friedman which divides the legal system into three components: legal substance, legal structure, and legal culture. This research is an empirical research with a qualitative method supported by spatial analysis through an overlay technique between the spatial pattern map of the RTRW and the distribution of the coordinate points of accommodation facilities. The results of the study show that from the aspect of legal substance, Karanganyar Regency has comprehensive spatial regulations through Regional Regulation Number 1 of 2013 jo. Number 19 of 2019. In terms of legal structure, the overlay analysis revealed that of the 170 units of accommodation facilities, 142 units (83.5%) were in the appropriate zone, but 28 units (16.5%) were still found in dryland agricultural zones and protected areas. The interview confirmed that permit verification and field supervision have not been running optimally. From the aspect of legal culture, investment decisions are based more on economic considerations (proximity to tourist attractions) than compliance with RTRW zoning. This study concludes that the effectiveness of controlling the use of space requires the simultaneous strengthening of three components of the legal system: enhancement of substance, optimization of structure through spatial-based supervision, and transformation of legal culture through consistent enforcement of sanctions.